2014
DOI: 10.3928/00989134-20131028-08
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effects of TAI CHI for the Promotion of Sleep Quality and Quality of Life: A Single-Group Study in a Sample of Older Chinese Individuals in Hong Kong

Abstract: Poor sleep in later life is a global issue that reduces many individuals' quality of life (QOL). The purpose of this pilot study was to test the feasibility and effects of a simplified tai chi exercise intervention on sleep quality and QOL among Chinese community-dwelling older adults with poor sleep quality. This single-group, descriptive feasibility study included 34 individuals with poor sleep quality who agreed to participate in a 12-week tai chi intervention. Twenty-six individuals completed the program (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…e articles using longitudinal data were primarily focused on physical health (62.5%), depression (12.5%), quality of life (12.5%), and cognitive function (12.5%). e exercises adopted in the studies were Tai Chi (33), physical exercise (10), square dancing (4), swimming (2), walking (2), outdoor cycling (1), light volleyball (1), and low-impact exercise (2), while 13 of them did not specify the exercise. Most of the studies used the following questionnaires for data collection: the International Physical Activity Questionnaire (13)…”
Section: Cohort Studymentioning
confidence: 99%
See 1 more Smart Citation
“…e articles using longitudinal data were primarily focused on physical health (62.5%), depression (12.5%), quality of life (12.5%), and cognitive function (12.5%). e exercises adopted in the studies were Tai Chi (33), physical exercise (10), square dancing (4), swimming (2), walking (2), outdoor cycling (1), light volleyball (1), and low-impact exercise (2), while 13 of them did not specify the exercise. Most of the studies used the following questionnaires for data collection: the International Physical Activity Questionnaire (13)…”
Section: Cohort Studymentioning
confidence: 99%
“…e physical activity interventions adopted were 12-26 weeks of aerobic exercise, Tai Chi, dumbbell exercise, Baduanjin, dance, elastic band resistance exercise or the Qigong intervention program. e intervention studies found that older adults showed less perceived stress, a better quality of sleep and a higher con dence level in their self-rated health (33). Overall, their psychological wellbeing improved aer participating in physical activity (34).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Research has shown that Tai Chi might be helpful for health-related fitness, by reducing blood pressure, controlling blood lipids and decreasing blood glucose, 45 46 as well as improving balance control, 47 cardiopulmonary function, 48 quality of sleep and quality of life. 49 However, most of the recent systematic reviews’ results have suggested that larger scale studies with more participants and longer observation periods are necessary to further confirm and illuminate the effectiveness of Tai Chi. 50 51 …”
Section: Discussionmentioning
confidence: 99%